Understanding patient satisfaction and loyalty in public and private primary health care - Febri Endra Budi Setyawan; Stefanus Supriyanto; Ernawaty; Retno Lestari (Journal of Public Health Research, 2020)
Background: The quality of health centers, patient satisfaction, and loyalty are three key factors that enable health care providers to improve their services and cost-effectiveness. This study, therefore, aims to determine patient satisfaction and loyalty in public and private primary health care centers. D esign and Methods: Data were obtained from a cross-sectional design of 1470 self-administered questionnaires and analyzed based on mean, standard deviation, and correlation coefficients. Results: The results showed respectively a strong and moderate correlation between patient satisfaction and loyalty in private (r=0.767) and public (r=0.54) primary health care centers, respectively. In addition, in both centers patients received adequate medical services, with social aspects as the least important factors affecting patient satisfaction. Conclusions: In conclusion, primary health care practices need to recognize the needs that influence patients’ satisfaction and loyalty, to improve the quality of their services.